The circadian clock protein BMAL1 regulates IL-1β in macrophages via NRF2 - EARLY, JAMES ORMAN (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2018)
The response of the innate immune system to an inflammatory insult is largely dependent on time-of-day, and many inflammatory conditions are associated with dysfunctional molecular clocks within immune cells. However, the mechanisms governing such responses have yet to be fully characterized. In this study, I have discovered a novel immunomodulatory role for the core molecular clock protein BMAL1. I have demonstrated that BMAL1 drives expression of the major antioxidant transcription factor, NRF2, in macrophages. In doing so it promotes diurnal variation in anti-oxidant and oxidative stress/ROS regulation. Deletion of Bmal1 in macrophages results in decreased NRF2 activity and antioxidant response, facilitating accumulation of oxidative stress. Lack of BMAL1 may also facilitate increased ROS production via alterations to cellular metabolism. Deletion of Bmal1 results in increased glycolysis and oxidative phosphorylation in response to LPS stimulation. The increased ROS in macrophages lacking BMAL1 is produced mainly from the mitochondria, supporting the theory of BMAL1 mediated regulation of metabolism as a regulator of oxidative stress. NRF2 plays a critical role in the innate immune system, limiting inflammation via reactive oxygen species (ROS) suppression and direct repression of the pro-inflammatory cytokines IL-1β and IL-6. Lack of NRF2 in Bmal1 deficient cells facilitates excess production of ROS, stabilising the hypoxic response protein HIF-1a. Increased ROS and HIF-1a levels, as well as decreased repressive activity of NRF2 in cells lacking BMAL1, results in increased production of the pro-inflammatory cytokine IL-1β. Deletion of Bmal1 also increases cleavage of IL-1β and cell death by the inflammasome, which appears to be at least partially mediated by oxidative stress. In summary, I have uncovered novel roles for BMAL1 in macrophages, both as a regulator of metabolism and inflammation. These discoveries have implications in terms of treatment of inflammatory disorders that display circadian rhythmicity, and in the increasing number of inflammatory driven pathologies arising from our 24 hr modern society.
APPROVED
Keywords: Circadian, molecular clock, inflammation, oxidative stress, BMAL1, NRF2